Informal institutions’ influence on FDI flows: A configurational fsQCA analysis of corruption as part of the MNEs’ FDI motivation system - Jae Kim (International Business Review, 2024)
Previous research has emphasised the importance of examining institutional influences on FDI attractiveness. There is, however, relatively limited, conflicting, research exploring the relationship between informal institutional effects, such as level of corruption, and FDI motivation. Addressing this gap, we adopt a configurational fsQCA-based approach to link informal institutional influences to FDI motivation driving the presence or absence of FDI flows. Conceptualising corruption as bribery and unfair business practices, we extend our understanding of informal institutional quality impact on FDI inflows. Results reveal that informal institutional effects on FDI vary across regions, with several pathways explaining the presence or absence of FDI, according to the presence or absence of corruption. We add to previous studies by identifying the conditions that, when combined with corruption, are linked to the presence or absence of FDI. Results also indicate that whilst corruption appears unimportant in preventing FDI, and is of only secondary importance in driving FDI, it appears to have importance in determining the type of MNEs’ undertaking FDI. Overall, corruption is likely determining which companies invest in a country, rather than if, traditional reasons for FDI, particularly Resource and Market seeking, being key, with strategic and efficiency-seeking also being of secondary importance.